International relations since the end of the Cold War new and old dimensions - Lundestad, Geir, 1945- (Oxford : Oxford University Press, 2013)
In'International Relations Since the End of the Cold War' many of the world's leading scholars examine the Cold War legacy. The authors examine several key issues including: the relationship between democracy and peace, the Cold War and the Third World superpowers, the role of post-Cold War nuclear weapons.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Keywords: World politics -- 1989-; History, Modern -- 1989-; International relations